2017
DOI: 10.1016/j.chemosphere.2017.01.128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various cheese whey treatment scenarios in single-chamber microbial electrolysis cells for improved biohydrogen production

Abstract: In this study single-chamber microbial electrolysis cells (MECs) were applied to treat cheese whey (CW), an industrial by-product, and recover H gas. Firstly, this substrate was fed directly to the MEC to get the initial feedback about its H generation potential. The results indicated that the direct application of CW requires an adequate pH control to realize bioelectrohydrogenesis and avoid operational failure due to the loss of bioanode activity. In the second part of the study, the effluents of anaerobic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 53 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…The performance of a wide range of bioprocesses can be largely improved if hybridized with bio-electrochemical systems [58], as seen in Figure 8. Though MFCs could have the potential to process wastes of the food industry e.g., cheese whey [53], treatments prior to the bio-electrochemical systems may further improve their working efficiency on such substrates [54,55]. A cornerstone of wastewater e.g., fermentation effluent management in MFCs, is the electrical conductivity of the solution, which is often low and may reduce the power density.…”
Section: Bes In Complex Systemsmentioning
confidence: 99%
“…The performance of a wide range of bioprocesses can be largely improved if hybridized with bio-electrochemical systems [58], as seen in Figure 8. Though MFCs could have the potential to process wastes of the food industry e.g., cheese whey [53], treatments prior to the bio-electrochemical systems may further improve their working efficiency on such substrates [54,55]. A cornerstone of wastewater e.g., fermentation effluent management in MFCs, is the electrical conductivity of the solution, which is often low and may reduce the power density.…”
Section: Bes In Complex Systemsmentioning
confidence: 99%
“…They were also the first to report a strong influence of temperature on biohydrogen production, with the lowest temperature (15 °C) showing the best results (1.12 mol H 2 per mol lactose). Rivera et al ( 24 ) showed that microbial electrolysis cells can be considered for the treatment of cheese whey to obtain biohydrogen. Blanco et al ( 25 ) described the anaerobic structured-bed reactor (ASTBR) as a likely alternative for fermentative biohydrogen production from cheese whey, offering better performances than conventional fixed-bed reactors.…”
Section: Sustainable Utilization Of Whey and Its Componentsmentioning
confidence: 99%
“…Rivera et al (24) showed that microbial electrolysis cells (MECs) can be considered for the treatment of cheese whey to obtain biohydrogen. Blanco et al (25) described the anaerobic structured-bed Please note that this is an unedited version of the manuscript that has been accepted for publication.…”
Section: Biogasmentioning
confidence: 99%